The Closer, The Harder? Investigating the use of peripheral vision in 3vs3 counter-attack VR situations in football - Božo Vukojević; Svitlana Pinchuk; Christian Vater (Current Issues in Sport Science)
Introduction: Peripheral vision has been reported to be functional in team sports when monitoring the movements of multiple players (Vater et al., 2019). Expert soccer players for example report to use their peripheral vision in 3 vs. 3 football situations (Vater et al., 2019). It seems that they anchor their gaze on the player's possession of the ball to monitor peripheral events (e.g., movements of other players). In this experimental study, we challenged the use of peripheral vision by varying the distance between the direct opponent and the participant in a virtual-reality counterattack situation.